84.9k views
5 votes
Given y2 + 5y - 6 = (y + p)(y +q) find the
values of p and q.

User Jayqui
by
5.9k points

1 Answer

3 votes

Answer:

p = 6, q = - 1

Explanation:

Factor the left side and compare to right side

y² + 5y - 6

Consider the factors of the constant term (- 6) which sum to give the coefficient of the y- term (+ 5)

The factors are + 6 and - 1, since

6 × - 1 = - 6 and 6 - 1 = + 5, thus

y² + 5y - 6 = (y + 6)(y - 1)

Compare with (y + p)(y + q) , then

p = 6 and q = - 1

User Michou
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.